2020
DOI: 10.1111/apce.12283
|View full text |Cite
|
Sign up to set email alerts
|

Lean HRM practices in work integration social enterprises: Moving towards social lean production. Evidence from Italian case studies*

Abstract: * Our thanks go to the organizations and to the people who have participated in the interview for this research. We also thank Flaviano Zandonai for his early suggestions on relevant cases. Finally, we would like to thank the Editors of this Journal and the two anonymous reviewers for their helpful comments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Portals and microblogs call themselves new media, Internet and TV call themselves new media, and paper media has also been revised to dress up as new media. is chaotic situation is in line with the prediction of American communication scholar Schramm: "the basic nature of human communication will not change, but the social system of communication itself is likely to be different from that in previous periods" [3]. To define new media from the perspective of communication, "new media" should have the communication characteristics that traditional media do not have.…”
Section: Introductionmentioning
confidence: 53%
“…Portals and microblogs call themselves new media, Internet and TV call themselves new media, and paper media has also been revised to dress up as new media. is chaotic situation is in line with the prediction of American communication scholar Schramm: "the basic nature of human communication will not change, but the social system of communication itself is likely to be different from that in previous periods" [3]. To define new media from the perspective of communication, "new media" should have the communication characteristics that traditional media do not have.…”
Section: Introductionmentioning
confidence: 53%
“…ey proposed a hybrid ensemble machine learning approach by incorporating two classic machine learning approaches, the RS (random subspace), and multiboosting. e work in [17] used the standard probit algorithm along with various machine learning algorithms like neural networks and KNN. ey achieved a lower error rate with the machine learning techniques as compared to the classic methods used for credit risk assessment.…”
Section: Related Workmentioning
confidence: 99%
“…While HRM practices are recognized as necessary for LP adoption and sustainability, they have seldom been studied in the literature. The few works [2,6,[19][20][21] that investigated these practices stressed their contribution to the success of LP initiatives and concluded that companies contemplating a transition from mass production to LP should consider, among other things, the HRM practices used by Toyota, and adapt them to their organizational context and sector of activity.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it provides them with different training approaches to improve their skills, including classroom training (i.e., developing an understanding of basic concepts), on-the-job development (i.e., learning by doing) and personal training opportunities (i.e., training is requested by the employee to meet a specific learning need) [8]. These trainings are designed to educate employees about the main challenges and opportunities of LP adoption and to provide them with the necessary knowledge on LP principles and methods [21]. Once employees understand the objective of LP and learn how to use its tools and techniques, their participation in the continuous improvement process becomes easier [21].…”
mentioning
confidence: 99%